INFLUENCE OF OWNER'S PERCEPTION, SMALL AND MEDIUM BUSINESS ACCOUNTING KNOWLEDGE ON THE USE OF ACCOUNTING INFORMATION - Risawati Risawati; Nurul Azizah; Djojo Dihardjo (Journal of Industrial Engineering & Management Research, 2022)
The contribution of small and medium-sized enterprises (SMEs) to the economy has indeed been proven, but on the other hand, business actors of this scale also still face many problems, and one of them is in managing their finances, especially in using accounting information in making various decisions. The manager's perception is strongly suspected to be one of the keys. This study aims to obtain information about the perceptions and accounting knowledge of SMEs, and their effect on the use of accounting information for decision making. This research was conducted by using the object of SME owners in the Mojokerto Regency area, which were selected and surveyed randomly. The analysis was carried out descriptively using Chi Square analysis. . The influence test also shows that there is a significant relationship that the perception and knowledge of SMEs about accounting will affect the use of existing accounting information. This study uses the Classical Assumption Test, namely Normality Test, Multicollinearity Test, Auto Correlation Test and Heteroscedasticity Test, Correlation analysis, Multiple Linear Regression analysis and Hypothesis Testin